Expanding the role of Australian pharmacists in community pharmacies in chronic pain management - a narrative review - Mishriky J; Stupans I; Chan V (Centro de Investigaciones y Publicaciones Farmaceuticas, 2019)
Chronic pain is a condition where patients continuously experience pain symptoms for at least 3 to 6 months. It is one of the leading causes of disabilities across the globe. Failure to adequately manage chronic pain often results in additional health concerns that may directly contribute to the worsening symptoms of pain. Community pharmacists are an important healthcare resource that contributes to patient care, yet their roles in chronic pain management are often not fully utilised. This review aimed to investigate and explore pharmacist-driven chronic pain educational and medication management interventions in community pharmacies on an international level, and thereby identify if there are potential benefits in modelling and incorporating these interventions in the Australian community. We found a number of studies conducted in Europe and the United States investigated the benefits of pharmacist-driven educational and medication management interventions in the context of chronic pain management. Results demonstrated that there were improvements in the pain scores, depression/anxiety scales and physical functionality in patient groups receiving the pharmacist driven-interventions, thereby highlighting the clinical benefit of these interventions in chronic pain. In conclusion, pharmacists are trustworthy and responsible advocates for medication reviews and patient education. There are currently very limited formal nationally recognised pharmacist-driven intervention programs dedicated to chronic pain management in Australian community pharmacies. International studies have shown that pharmacist-driven chronic pain interventions undertaken in community pharmacies are of benefit with regards to alleviating pain symptoms and adverse events. Furthermore, it is also clear that research around the application of pharmacist-led chronic pain interventions in Australia is lacking. Modelling interventions that have been conducted overseas may be worth exploring in Australia. The implementation of similar intervention programs for Australian pharmacists in community pharmacies may provide enhanced clinical outcomes for patients suffering from chronic pain. The recently implemented Chronic Pain MedsCheck Trial may provide some answers.